Pengaruh Imam Desa Dalam Peningkatkan Kesadaran Beragama Masyarakat Di Kec. Libureng Kab. Bone - Arisal, Muhammad (JURNAL AL-QAYYIMAH, 2019)
This research is a field research with a type of quantitative research that is examining and researching the sources of respondents found directly in the field through the results of observation, interviews and documentation with percentages in the form of numbers. The approach in this thesis is the normative theological approach, the paedagogical approach and the sociological approach. Data analysis technique used is simple linear regression analysis which is linear relationship between one independent variable and independent variable.The results showed that the role of imam mosque in the community in aspects of religious education, religious activities and their role in society showed a score of 188 out of 300 maximum scores. In the scale of the percentage is classified 63% very good 29% enough value and 8% bad value. The role of mosque imam is at 63% with very good value ie mosque imam plays an active role. Libureng community awareness level of 10 respondents with score 100, with classification of 72%, 20% and 8%. The results show that the awareness of the masses is in the 72% (very good) procession. The correlation between the role of the imam of the mosque and the level of public awareness seems to be in line and relevant, so the imam of the mosque is very instrumental in increasing the awareness of the community in Libureng Subdistrict, Bone Regency.